The effect of pesticide residue on mortality and fecundity of Elaeidobius kamerunicus (Coleoptera: Curculionidae). Issue 1 (March 2020) - Setyawan, Y P; Naim, M; Advento, A D; Caliman, J P
Abstract: The effect of pesticide residue (acaricide, insecticides, herbicides, and fungicides) commonly used in oil palm plantations was assessed to pollinating weevil, Elaeidobius kamerunicus under laboratory condition. The study showed that all insecticides and acaricide in the spikelet were harmful to the weevil, causing mortality ranged from 37% to 100% application. Dimehypo, carbosulfan and deltamethrin cause 100% mortality at 10 hr after treatment (HAT) followed by fipronil, acephate, pyridaben, imidacloprid and Bacillus thuringiensis cause 87%, 83%, 60%, 40% and 37% mortality at 10 HAT respectively. Our study also revealed that all herbicides recidu in the spikelet had a negative impact on the weevil. Metsulfuron-methyl caused the highest mortality (83%) of the weevils death, followed by triclopyr, ammonium glufosinate, glyphosate, and fluroxyphyr caused 63%, 43%, 33% and 30% at 10 HAT, respectively. Fungicides also had negative impact with lower extent. Exposing mancozeb was causing 27% mortality, significantly higher than benomyl (13%). Further analysis showed that acaricide and insecticides significantly reduce fecundity of the weevil except for B. thuringiensis, herbicides, and fungicides. The study suggests that choosing correct active ingredients would maintain sustainable number of weevil in oil palm plantation and would avoid the declining regeneration effect of pollinating weevil.